2022
DOI: 10.1007/s11033-022-07714-5
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide increases heat shock proteins in extracellular vesicles released from glioblastoma cells

Abstract: Background: Glioblastoma (GBM) is the most malignant and the fastest-progressing type of primary brain tumours. Temozolomide (TMZ) is a chemotherapeutic drug for the treatment of GBM. Extracellular vesicles (EVs) have been recently con rmed to have a substantial role in the GBM, and their contents released from GBM cells have been considered a target for treatment. The purpose of this study is to evaluate the impact of TMZ on heat shock proteins (HSPs) derived from EVs originated from GBM cell lines (U87-MG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Kıyga et al [78] showed that the amount of CD63 in the EVs of TMZ (200 µM)treated GBM cells increased, however, without any statistically significant difference. Ricklefs et al [79] demonstrated that EVs with double positive tetraspanin expression (CD63 + /CD81 + ; CD9 + /CD81 + ) were enriched in GBM cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…Kıyga et al [78] showed that the amount of CD63 in the EVs of TMZ (200 µM)treated GBM cells increased, however, without any statistically significant difference. Ricklefs et al [79] demonstrated that EVs with double positive tetraspanin expression (CD63 + /CD81 + ; CD9 + /CD81 + ) were enriched in GBM cell lines.…”
Section: Discussionmentioning
confidence: 98%
“… CircBACH1/ miR-217/G3BP2 axis a new regulatory for PTX-resistance and progression of breast cancer. 672 Cisplatin Ovarian cancer cells A2780, IGROV-1 cells Ovarian cancer CREB, ERK, JNK, p38α, p53 inhibits ovarian cancer 673 , 674 Milk exosomes loaded with cisplatin A2780, nu/nu mice Ovarian cancer ARF6, Rac1, CLTC, caveolin Overcomes cisplatin-resistance in ovarian cancer Temozolomide Glioblastoma cells U87-MG cells, GBM cells Glioblastoma Heat shock protein, RAD51, MDM2 Leads to cell adhesion 675 EVs encapsulated miR-153-3p LUAD cells NCI-H1993, SW1271, BALB/c mice, Lung adenocarcinoma BANCR, miR-153-3p, PI3K/AKT Increases cell invasion 676 EVs PDAC cells MIA PaCa-2, PANC-1,Rag2 −/− Ilrg2 −/−, mice Pancreatic ductal adenocarcinoma Rab27a, LRP-4 receptor, YAP Intratumor communication Targeted therapy for PDAC 677 EVs Human Liver Stem Cells MSCs Renal cancer cells SCID mice Renal cell carcinoma miR-Let7b, miR-200b, miR-200c and miR-223, EGFR, ZEB1, ZEB2, MMP1 antitumor effects 678 …”
Section: Role Of Extracellular Vesicles In Diseases Other Than Cancermentioning
confidence: 99%
“…In a combined TMZ plus an HSP90 inhibitor (geldanalmycin) treatment, there were more glioblastoma cells undergoing apoptosis and diminished vesiculation [72]. Kıyga et al observed increased expression of HSP70, HSP60, HSP90, and HSP27 (HSPB family) on EVs derived from glioblastoma cells after treatment and this increased expression was related to therapeutic resistance [73]. Lv et al showed that chemotherapeutic treatment of hepatocarcinoma cells, HepG2 and PLC/PRF/5, increases secretion of exosomes expressing HSP60, HSP70, and HSP90 on their membranes.…”
Section: Transfer Of Therapy Resistance Mediated By Hsp-evs' Release ...mentioning
confidence: 99%